Effect of sodium caseinate on fiber disappearance and fermentation parameters using an equine cecal inoculum - Taylor, Shelbey J.; Fehlberg, L.K.; Drouillard, James S.; Douthit, Teresa L.; Lattimer, James M. (My University, 2018)
Improving fiber digestion of a low quality forage via protein supplementation has been demonstrated in cattle in a multitude of studies. Therefore, it was theorized that similar effects may be observed in the equine. Cecal fluid collected from 4 cecally cannulated Quarter Horses was used to examine the effect of protein supplementation on fiber disappearance and fermentation parameters in vitro. Fermentation bottles containing McDougall’s buffer and strained and stratified cecal fluid were used in a 2 x 5 factorial with four replications (horse). Factors consisted of substrate (alfalfa and native prairie hay) and supplemental crude protein supplied via sodium caseinate (0%, 0.5%, 1.0%, 2.0%, and 4.0% additional CP). Bottles were incubated for 48 h, at which time fluid and digesta was collected for pH, DM, NDF, ADF, and VFA analyses. Alfalfa had greater (p <0.05) NDF and ADF disappearance when compared to prairie hay. Similarly, total VFA production was greater (p <0.05) for bottles containing alfalfa. Sodium caseinate had no effect on pH, DM, NDF, ADF, or total VFA concentration in bottles containing alfalfa. Bottles containing prairie hay and supplemented with 0.5%, 1.0%, 2.0%, and 4.0% CP from sodium caseinate had a reduced (p <0.05) pH when compared to control. Dry matter, NDF, and ADF disappearance were greater (p <0.05) in bottles containing prairie hay supplemented with 1.0%, 2.0%, and 4.0% CP when compared to control. In bottles containing prairie hay, total VFA increased (p <0.05) with the addition of 4.0% CP from sodium caseinate when compared to control. No differences were observed for any response variable between 2.0% and 4.0% additional CP. Results from this study show that fiber disappearance can be enhanced by supplementing sodium caseinate to a low protein forage. This is likely a result of increase in microbial fermentation activity and/or population. As expected, alfalfa is more easily digested by the microflora of the cecum thus producing a greater VFA production. This would most likely yield a greater DE (Mcal/kg) to the equine.
Keywords: Spring 2018